An Overview of School Recess: What Children Think and Feel - Ana Lucía Chaves-Álvarez (Universidad Nacional, Costa Rica, 2013)
Researchers of the Institute for Interdisciplinary Studies of Childhood and Adolescence (INEINA) have been interested in studying the current activities developed during recess time in public schools and what children require for this period from the point of view of the child population. This paper is the result from a research conducted on this matter with the participation of a group of children, in order to collect ideas from the participants and provide recommendations on possible strategies to enhance and strenghten recreation time at schools.